Chapter 1 Introduction "A Rapture So Pure That Its Words Are Tears" - Kellermann, Jonas (Taylor & Francis, 2021)
The introductory chapter frames Shakespeare's Romeo and Juliet and its dramatisation of romantic love within the recent affective turn, defining affect as relational and discursive movements that are intelligible as individual, nameable emotions based on their adherence to certain cultural taxonomies. This definition entails my overall query: what are the taxonomies according to which affective movements become readable as amorous emotion in Romeo and Juliet? To showcase that these patterns not only pertain to verbal language, I also discuss symphonic and balletic adaptations of the play, specifically Hector Berlioz's dramatic symphony Roméo et Juliette (1839) and Sasha Waltz's staging of the Berlioz's symphony for the Paris Opera Ballet (2007).